2019
DOI: 10.21608/jpp.2019.36262
|View full text |Cite
|
Sign up to set email alerts
|

Improving Sugar Pea Growth and Quality by using some Natural Substances

Abstract: Two field experiments were conducted at Private Farm in Wadi Al-Natroun Distrect, Beheira Governorate, Egypt during Winter seasons of 2016/2017 and 2017/2018, to study the effect of some natural foliar applications, i.e., fulvic acid (20 ml/l), effective microorganisms (5 ml/l),yeast extract (25 ml/l), humic acid (2 g/l), brassinolide (5 mg/l) and chitosan (200 mg/l) on vegetative growth, pod yield and quality of snow pea cultivar "Snow Wind" and sugar snap pea cultivar "Sugar Snap". The results showed that Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Meanwhile there was a significant decrease in impurities (ton ha -1 ) of sugar beet plants by increasing humic acid rates from zero up to 300 kg / ha. These results are in harmony with those obtained by Olk et al (2018) and El-Sayed et al (2019), who revealed that increasing humic acid made up a decrease in sodium, potassium, and amino nitrogen contents of sugar beet up to 300 kg ha -1 . Based on the obtained results, increasing humic acid level above 300 kg ha -1 , caused to increase of sodium and potassium concentrations in sugar beet.…”
Section: Soil Propertiessupporting
confidence: 90%
See 1 more Smart Citation
“…Meanwhile there was a significant decrease in impurities (ton ha -1 ) of sugar beet plants by increasing humic acid rates from zero up to 300 kg / ha. These results are in harmony with those obtained by Olk et al (2018) and El-Sayed et al (2019), who revealed that increasing humic acid made up a decrease in sodium, potassium, and amino nitrogen contents of sugar beet up to 300 kg ha -1 . Based on the obtained results, increasing humic acid level above 300 kg ha -1 , caused to increase of sodium and potassium concentrations in sugar beet.…”
Section: Soil Propertiessupporting
confidence: 90%
“…The importance of this crop comes from its growing in the newly reclaimed land and giving a high sugar recovery, as well as its lower water requirement. Moreover, sugar beet is specialized as a short duration crop, where its growth period is about half that of sugarcane (El-Sayed et al, 2019). Also, sugar beet being often, the most important cash crop in the rotation, it leaves the soil in good conditions for the following summer cereal crop (Nemeata et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Artyszak et al (2015) reported that foliar application of silicon had no significant effect on sugar beet roots impurities parameters (N, P, and K) in both seasons. El-Sayed et al (2019) revealed that increasing potassium silicate made up a decrease in sodium, potassium and amino nitrogen contents of sugar beet varieties up to 300 kg. ha.…”
Section: Sugar Yield and Juice Quality Traitsmentioning
confidence: 99%
“…Shaban et al, (2014) indicated that the addition of 10 kg humic acid/fed as a soil application significantly increased, N, P, and K percentages in sugar beet root in both seasons. Olk et al, (2018) and El-Sayed et al, (2019), who revealed that increasing humic acid made up a decrease in sodium, potassium, and amino nitrogen contents of sugar beet varieties up to 300 kg. ha.…”
Section: Impurities Traitsmentioning
confidence: 99%